MDACl2-Modified SnO2 Film for Efficient Planar Perovskite Solar Cells - Yaodong Xiao; Xiangqian Cui; Boyuan Xiang; Yanping Chen; Chaoyue Zhao; Lihong Wang; Chuqun Yang; Guangye Zhang; Chen Xie; Yulai Han; Mingxia Qiu; Shunpu Li; et al. (Molecules, 2023)
The electron transport layer (ETL) with excellent charge extraction and transport ability is one of the key components of high-performance perovskite solar cells (PSCs). SnO2 has been considered as a more promising ETL for the future commercialization of PSCs due to its excellent photoelectric properties and easy processing. Herein, we propose a facile and effective ETL modification strategy based on the incorporation of methylenediammonium dichloride (MDACl2) into the SnO2 precursor colloidal solution. The effects of MDACl2 incorporation on charge transport, defect passivation, perovskite crystallization, and PSC performance are systematically investigated. First, the surface defects of the SnO2 film are effectively passivated, resulting in the increased conductivity of the SnO2 film, which is conducive to electron extraction and transport. Second, the MDACl2 modification contributes to the formation of high-quality perovskite films with improved crystallinity and reduced defect density. Furthermore, a more suitable energy level alignment is achieved at the ETL/perovskite interface, which facilitates the charge transport due to the lower energy barrier. Consequently, the MDACl2-modified PSCs exhibit a champion efficiency of 22.30% compared with 19.62% of the control device, and the device stability is also significantly improved.